Peces-Barba, Latin America and human rights - Squella, Agustín (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2023)
This article reflects on the importance of raising awareness of human rights in Latin America. The author mentions that outside academic circles and human rights organisations, little is known about human rights, their concept, foundations, history, and protection systems in this part of the world. The author highlights Gregorio Peces-Barba’s enlightening, popularising work in the legal and political culture of Spain and abroad and argues that something similar needs to be done in Latin America. The author of this article mentions that in Chile, the human rights issue has recently returned to the forefront in the context of the constituent process and there have been very interesting public debates on fundamental rights, including those of a social nature.
Keywords: human rights; legal culture; politics